Impact of Nanosized CuO Insertion on Structural and Mechanical Properties of PVA: HPMC Based Polymer Blend Nanocomposites - Vijayashree, K.; Sheshappa Rai, K. (Asian Journal of Chemistry, 2021)
Insertion of metal-oxide nanoparticles to polymers stipulate the modification of physical properties of polymers over and above the accomplishment of new features in the polymer matrix. In the current study, an attempt was made to disperse the CuO nanoparticles in the polyvinyl alcohol and hydroxypropyl methylcellulose (HPMC) blend to investigate the structural, mechanical and optical properties of the nanocomposite. Blend was prepared in different ratios using PVA and HPMC, viz. 25:50, 50:50 and 75:25 wt%. The CuO nanoparticles were added to the 75:25 PVA:HPMC blend in different percentage like 0.5,1 and 1.5%. The polymer with and without CuO incorporation were subjected to X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, UV-visible spectral analyses and mechanical strength, etc. The results revealed that the incorporation of the CuO nanoparticles enhanced the structural and mechanical properties of the polymer by forming successful nanocomposite.